Synthesis of epoxidized palm oil-based trimethylolpropane ester by in situ epoxidation method - Naidir, Ferra; Yunus, Robiah; Mohd. Ghazi, Tinia Idaty; Ramli, Irmawati (Universiti Putra Malaysia Press, 2012)
Palm oil-based Trimethylolpropane ester (TMP ester), with an iodine value of 66.4 g/100g, was epoxidized to produce epoxidized TMP esters. In situ epoxidation method was used with peracetic acid to eliminate fatty acid double bonds in palm oil-based TMP ester and change it into oxirane ring. This was done to improve the oxidative stability of trimethylolpropane ester which is a key concern limiting the useful service life in lubricants. The epoxidation was performed by reacting acetic acid as active oxygen carrier with concentrated hydrogen peroxide as oxygen donor and a small amount of homogeneous catalyst (sulphuric acid). The effects of various parameters on the rate of epoxidation (such as the ratio of mole acetic acid to ethylenic unsaturation, hydrogen peroxide to ethylenic unsaturation and acetic acid mole ratio, and amount of catalyst) were studied. The rate of oxidation was investigated by the percentage of oxirane oxygen analysis and iodine value.